A Magnetic Resonance Measurement Technique for Rapidly Switched Gradient Magnetic Fields in a Magnetic Resonance Tomograph - K. Bartušek; E. Gescheidtová (Acta Polytechnica, 2003)
This paper describes a method for measuring of the gradient magnetic field in Nuclear Magnetic Resonance (NMR) tomography, which is one of the modern medical diagnostic methods. A very important prerequisite for high quality imaging is a gradient magnetic field in the instrument with exactly defined properties. Nuclear magnetic resonance enables us to measure the pulse gradient magnetic field characteristics with high accuracy. These interesting precise methods were designed, realised, and tested at the Institute of Scientific Instruments (ISI) of the Academy of Sciences of the Czech Republic. The first of them was the Instantaneous Frequency (IF) method, which was developed into the Instantaneous Frequency of Spin Echo (IFSE) and the Instantaneous Frequency of Spin Echo Series (IFSES) methods. The above named methods are described in this paper and their a comparison is also presented.